2016
DOI: 10.1016/j.redox.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic and antimalarial effects of tight-binding glyoxalase 1 inhibitors on the host-parasite unit of erythrocytes infected with Plasmodium falciparum

Abstract: Glyoxalases prevent the formation of advanced glycation end products by converting glycolysis-derived methylglyoxal to d-lactate with the help of glutathione. Vander Jagt and colleagues previously showed that erythrocytes release about thirty times more d-lactate after infection with the human malaria parasite Plasmodium falciparum. Functional glyoxalases in the host-parasite unit might therefore be crucial for parasite survival. Here, we determined the antimalarial and hemolytic activity of two tight-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
(65 reference statements)
1
8
0
Order By: Relevance
“…In accordance with these results, a single IC 50 experiment with 3D7Δglo1 and 3D7Δcglo2 knockout strains and the Glo1 inhibitors compound 3 and 7 of our previous study 10 showed very similar IC 50 values compared to wild-type parasites (data not shown). If human Glo1 compensated for the loss of PfGlo1 in the 3D7Δglo1 knockout strains, one would expect altered IC 50 values because the inhibitors can also slowly inactivate the human enzyme 10 . Thus, parasite killing of wild-type and knockout strains at micromolar instead of nanomolar Glo1 inhibitor concentrations can be attributed to off-target effects.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In accordance with these results, a single IC 50 experiment with 3D7Δglo1 and 3D7Δcglo2 knockout strains and the Glo1 inhibitors compound 3 and 7 of our previous study 10 showed very similar IC 50 values compared to wild-type parasites (data not shown). If human Glo1 compensated for the loss of PfGlo1 in the 3D7Δglo1 knockout strains, one would expect altered IC 50 values because the inhibitors can also slowly inactivate the human enzyme 10 . Thus, parasite killing of wild-type and knockout strains at micromolar instead of nanomolar Glo1 inhibitor concentrations can be attributed to off-target effects.…”
Section: Discussionsupporting
confidence: 84%
“…The dispensability of PFGLO1 for parasite survival also explains the high IC 50 values of tight-binding Glo1-inhibitors in previous cell culture experiments 10 in contrast to low nanomolar inhibition constants against recombinant PfGlo1 9 . In accordance with these results, a single IC 50 experiment with 3D7Δglo1 and 3D7Δcglo2 knockout strains and the Glo1 inhibitors compound 3 and 7 of our previous study 10 showed very similar IC 50 values compared to wild-type parasites (data not shown). If human Glo1 compensated for the loss of PfGlo1 in the 3D7Δglo1 knockout strains, one would expect altered IC 50 values because the inhibitors can also slowly inactivate the human enzyme 10 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations